One-way rotation of a chemically anchored single molecule-rotor. Issue 38 (22nd September 2021) - Eisenhut, Frank; Kühne, Tim; Monsalve, Jorge; Srivastava, Saurabh; Ryndyk, Dmitry A.; Cuniberti, Gianaurelio; Aiboudi, Oumaima; Lissel, Franziska; Zobač, Vladimír; Robles, Roberto; Lorente, Nicolás; Joachim, Christian; et al.
Abstract : Superimposed STM images of the six stable rotation stations of a DMBI-P molecule during a step by step clockwise rotation induced by voltage pulses ( V = 0.5 V, I = 0.5 nA, t = 10 s). Abstract : We present the chemical anchoring of a DMBI-P molecule-rotor to the Au(111) surface after a dissociation reaction. At the temperature of 5 K, the anchored rotor shows a sequential unidirectional rotational motion through six defined stations induced by tunneling electrons. A typical voltage pulse of 400 mV applied on a specific location of the molecule causes a unidirectional rotation of 60° with a probability higher than 95%. When the temperature of the substrate increases above 20 K, the anchoring is maintained and the rotation stops being unidirectional and randomly explores the same six stations. Density functional theory simulations confirm the anchoring reaction. Experimentally, the rotation shows a clear threshold at the onset of the C–H stretch manifold, showing that the molecule is first vibrationally excited and later it decays into the rotational degrees of freedom.